1995
DOI: 10.1364/ol.20.000683
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photorefractive-index changes in annealed-proton-exchanged channel waveguides in MgO-doped and congruent LiNbO_3

Abstract: A quantitative comparison of the photorefractive effect in annealed proton-exchanged channel waveguides in MgO-doped and congruent LiNbO(3) at the wavelengths of 633 and 830 nm is presented. An accurate measurement technique is described to measure the refractive-index change as a function of time and the guided mode intensity for different wavelengths. The results show that doping with 7% MgO reduces the photorefractive effect at a wavelength of lambda = 633 nm by 2 orders of magnitude. The photorefractive ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This agrees well with the results reported in Ref. 5. In our experiment, the wavelength shift recovered perfectly to the original wavelength a few hours after the measurement, thus, the optical properties of the sample were not permanently damaged within our experimental conditions.…”
Section: Reducing Photorefractive Effect In Periodically Poled Zno-ansupporting
confidence: 93%
See 1 more Smart Citation
“…This agrees well with the results reported in Ref. 5. In our experiment, the wavelength shift recovered perfectly to the original wavelength a few hours after the measurement, thus, the optical properties of the sample were not permanently damaged within our experimental conditions.…”
Section: Reducing Photorefractive Effect In Periodically Poled Zno-ansupporting
confidence: 93%
“…4 A reduction of the photorefractive-index change in an annealed proton exchanged ͑APE͒ waveguide using MgO-doped LiNbO 3 has also been reported. 5 The damage resistance of this waveguide was demonstrated by blue second-harmonic generation ͑SHG͒ as high as 17 mW. 6 However, there is no quantifiable study on the photorefractive effect available for a periodically poled APE waveguide using MgO-or ZnO-doped LiNbO 3 .…”
Section: Reducing Photorefractive Effect In Periodically Poled Zno-anmentioning
confidence: 99%
“…Previous study has shown that APE waveguides in MgO-doped substrate are still affected by the photorefractive damage 17 . Therefore we prepared two samples with similar index profiles, one in CLN and the other in MgO-doped LN to compare their behaviour for increasing injected power.…”
Section: Waveguide Fabrication and Photorefractive Characterizationmentioning
confidence: 98%
“…A special interferometric set-up [12] based on a two-beam interference of the output beams of two simultaneously excited neighboring channel waveguides and improved with regard to a former publication [13] was used for the investigation of both the light-induced refractive index changes (commonly known as the photorefractive effect) and the electrooptic phase modulation. The experimental arrangement is shown in Fig.…”
Section: Light-induced Refractive Index Changesmentioning
confidence: 99%